Analysis Of User Behavior In Information Search Systems Design Of Recommendation Systems - Khurramova, Go'zal Ravshanovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the issues of analyzing user behavior (clicks, dwell time, search queries, etc.) in information retrieval and recommender systems. The paper analyzes methods for collecting implicit and explicit data, as well as the role of machine learning algorithms in generating personalized recommendations.